Goals in Argentinean adolescents: an exploratory research - Cattaneo, María Elisa (2008)
The present work examines the goals of life female and male argentinian adolescents have: they are aged 17 to 19, attending classes at school, living in the North, centre and the South of the country. This article refers to the importance of understanding adolescence as a process of autonomy in the present time. The aim is to investigate the characteristics of students' goals aforesaid loaded in 3687 protocols; to establish category of analisys, to define from theoretic framework and to illustrate the tipology to find. Also, to consider these articulated conditions, and to mention some subclases. From this point of view , we are considering the goals as the product of the individual activity. The fellow being a member of his community, the fellow that "thinks about himself", that yields according to specific ways to relate in his context. Moreover, these meanings link in one temporary- historical plot and they join to grow motivational patrons that incise into their life projects